2016
DOI: 10.1002/ejoc.201501520
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidative Coupling of Primary Amines under Air: A Flexible Route to Benzimidazole Derivatives

Abstract: Benzimidazoles are of fundamental importance in chemistry and biology, and the development of efficient, environmentally benign methods for their preparation remains a key challenge for organic chemists. In a biomimetic approach inspired by copper amine oxidases, we disclose herein the scope and factors influencing the success of the cooperative action of CuBr 2 as electron-transfer mediator and a topaquinone-like substrate-selective catalyst in the oxidative cyclocondensation of primary amines with o-aminoani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…13 C-NMR (400 MHz, CDCl 3 ) δ: 154.15, 153.21, 143.25, 136.83, 129.37, 127.51, 125.85, 122.80, 122.54, 119.98, 109.74, 35.08, 31.92, 31.46. The spectroscopic data match the previously reported data[39].…”
supporting
confidence: 90%
“…13 C-NMR (400 MHz, CDCl 3 ) δ: 154.15, 153.21, 143.25, 136.83, 129.37, 127.51, 125.85, 122.80, 122.54, 119.98, 109.74, 35.08, 31.92, 31.46. The spectroscopic data match the previously reported data[39].…”
supporting
confidence: 90%
“…Recently,our group has demonstrated that achiral N,N'-dioxide/Sc III complex [14] was able to catalyze the ringopening reaction of cyclopropyl ketones with amines efficiently,thus generating chiral 2,3-dihydropyrroles in excellent results.T he process is thought to proceed through nucleophilic ring opening of the cyclopropyl ketone to generate A, then intramolecular nucleophilic addition to afford the intermediate B,w ith subsequent dehydration to give the 2,3-dihydropyrrole product (path a, Scheme 1). [8a,h,k] Inspired by these results,werecently questioned whether it is possible to capture B by using another nucleophilie.W e envisaged that if 1,2-diaminobenzene was used as an ucleophilie,t he capture process might be brought to fruition through a5 -exo-tet cyclization [15] to give C,a nd would be facilitated by the good leaving ability of water (path b, Scheme 1). And then, C could undergo retro-Mannich [16] reaction to deliver the benzimidazole.Thus,astraightforward synthetic method for enantioenriched benzimidazole derivatives through acatalytic asymmetric ring opening/cyclization/ retro-Mannich sequence of cyclopropylk etones with benzene-1,2-diamines might be realized.…”
mentioning
confidence: 99%
“…The catalyst activates the α‐C─H bond of aliphatic primary amines ( 44 ) and forms imine via trans‐amination with N‐substituted o ‐phenylenediamines ( 43 ). Subsequent transimination and intramolecular cyclization form benzimidazoline, which later gets oxidized to afford the desired product (Scheme ) .…”
Section: Oxidative Coupling Of O‐phenylenediamine Using Transition Mementioning
confidence: 99%